FILM ANIMASI PENGENALAN SAHAM DENGAN METODE MOTION GRAPHIC - Eka Tripustikasari; Abednego Dwi Septiadi (Infotekmesin, 2019)
Investment is a principle thing in the business world, because investment is one source of capital that can be owned by capital holders. The public still has a perception that shares or capital markets or exchanges are something complicated, expensive and have high risk. A survey conducted by OJK in 2012 explained that the level of literacy and financial inclusion of Indonesian people was still relatively low at only 3.7 percent literacy and accountability. Only 0.11 percent is inversely proportional to the number of Indonesians whose numbers are always increasing every year. Let's Save Stocks is a campaign that was inaugurated in 2015 by Indonesian Vice President, Yusuf Kalla in enhancing the role of the community in shares. An interesting promotional media is needed to introduce shares to the public, one of which is an animated film that is able to be consumed by people of all ages, education and economics. Moreover, motion graphic is a technique that is able to make still images to move and be interactive.